Mass Spectrometry Metabolomics of Hot Steep Malt Extracts and Association to Sensory Traits. (2nd October 2021) - Bettenhausen, Harmonie M.; Barr, Lindsay; Omerigic, Heather; Yao, Linxing; Heuberger, Adam L.
Abstract: In the brewing industry, there is value in defining sensory attributes of malt, and recent protocols have been developed that enable analysis of aroma and taste. One method, the "hot steep, " is a hot water extract that is highly reproducible and able to distinguish malt flavor. However, the chemistry of the hot steep extracts has not been fully defined, and the links between specific metabolites of the hot steep and their resulting sensory attributes remains largely unknown. Here, a study was designed to describe the metabolite chemistry of hot steep extracts, and to characterize variation in this chemistry and corresponding sensory by comparative analysis of 12 commercial pale malts. Metabolomics was performed on the 12 malt hot steep extracts using three mass spectrometry platforms to detect volatiles (HS/SPME-GC-MS) and non-volatiles (UHPLC-TOF-MS and GC-MS). The analysis detected a total of 1, 026 compounds including lipids, organic acids, esters, and Maillard Reaction Products (MRPs), of which 162 compounds (15.7%) varied among the 12 hot steep extracts. Sensory of the 12 hot steep extracts was performed using an integrated Check All That Apply and quantitative analysis method for 14 traits, and the data revealed cereal, grassy, and dough aromas were the attributes that varied. The metabolomics and sensory data were integrated using OPLS analysis. The analysis revealed 64 compounds strongly associated with cereal aroma and included MRPs. A total of 23 compounds were strongly associated with grassy aroma including alkane/alkenes, benzenoids, organic acids, lipids, and fatty acid esters. Taken together, these data highlight the utility of the hot steep extract to differentiate malt for flavor and chemistry and indicate specific compounds that drive the most dominant flavors observed in this population of pale malts.